Hipertensi pada Diabetes Melitus: Patofisiologi dan Faktor Risiko - Vania Widyadhari Damayanti; Ade Yonata; Evi Kurniawaty (Medula, 2023)
Hypertension is a disease that commonly occurs in diabetes mellitus patients. There are 40 to 80 percent of DM patients who suffer from hypertension. Hypertension in diabetes mellitus increases the risk of cardiovascular complications. Even though there have been many studies that have proven that reducing blood pressure in diabetes mellitus patients has an effect on reducing the risk of cardiovascular complications, research shows that only 48 percent of the population can achieve a blood pressure target of less than 130/80 mmHg. The pathophysiology of hypertension in DM can be associated with a sedentary lifestyle, excess calorie intake, insulin resistance, dysregulation of the autonomic nervous system, premature vascular aging, increased intravascular volume, renal dysfunction, renin-angiotensin-aldosterone-system (RAAS), innate and acquired immunity, as well as environmental and socio-economic factors. Risk factors for hypertension in diabetes mellitus include age, gender, education, marital status, blood type, total cholesterol levels, HDL levels, LDL levels, triglyceride levels, smoking habits, employment, physical activity, body mass index, heredity of hypertension, DM heredity, and duration of suffering from DM, and blood glucose levels.